Pembelajaran Tematik, Pembelajaran Saintifik, dan Minat Belajar Siswa - Rusmini; Endi Sarwoko (Jurnal Penelitian dan Pendidikan IPS, 2020)
This research is motivated by the Government which requires the application of an integrated thematic 2013 curriculum. The scientific or scientific approach is believed to be the golden bridge of the development and development of students' attitudes, skills, and knowledge. This study aims to determine the effect of thematic learning and scientific learning on student interest both simultaneously and partially at MIN I Bulungan. The research method used is quantitative-statistics using Multiple Regression Analysis. The research population of students from grade 1 to grade VI totaling 601 students, with a sample of class VI students totaling 96 students. The results showed that simultaneously thematic learning and scientific learning had an effect on student interest in learning. Partially thematic learning and scientific learning affect the learning interest of students at MIN I Bulungan.